The Role of Motivation in Moderating the Influence of Organizational Culture and Work Discipline on Performance Employees at The Employment BPJS Se-Medan Raya - Afif, Muhammad Faruq; Ferine, Kiki Farida (Best Journal of Administration and Management, 2024)
This study aims to look at the role of motivation in moderating the influence of organizational culture and work discipline on employee performance at BPJS Ketenagakerjaan Se- Medan Raya. This type of research uses qualitative methods, this research was conducted at the BPJS Employment Branch Office in Greater Medan, the population used was 80 employees consisting of 20 personnel from Medan City, 20 personnel from North Medan, 20 personnel from Tanjung Morawa and 20 personnel from Binjai. The sample used is all the population of 80 employees with saturated samples being the sample technique. The data source used is primary data source and data collection by distributing questionnaires. This research model uses phat analysis and the measuring tool is the smart PLS version 3.3.3 application. The results of this study are as follows: Organizational culture has a positive and insignificant effect on employee performance with an original sample value of 0.042 and P values of 0.910. Organizational culture has a positive and significant effect on work motivation with an original sample value of 0.875 and p values of 0.000. Work discipline has a positive and insignificant effect on employee performance with an original sample value of 0.042 and p values of 0.851. Work discipline has a negative and significant effect on work motivation with an original sample value of -0.347 and p values of 0.000. Work motivation has a positive and significant effect on employee performance with an original sample value of 0.730 and p values of 0.000. Organizational culture has a positive and significant effect on employee performance through work motivation indirectly with original sample results of 0.634 and p values of 0.000. Work discipline has a negative and significant effect on employee performance through work motivation indirectly with an original sample value of -0.209 and p values of 0.006.